The electrochemical detection of tagged nanoparticles via particle-electrode collisions: Nanoelectroanalysis beyond immobilisation - Zhou, Y; Rees, N; Compton, R (2012)
The use of particle-impact coulometry in identifying and quantifying nanoparticles tagged (or labelled) with electroactive molecules is demonstrated via the detection of 1,4-nitrothiophenol-tagged silver nanoparticles in aqueous dispersion at potentials more negative than -0.17 V (vs. Ag/AgCl, the reduction potential of nitrothiophenol) via monitoring of particle-electrode collisions. This journal is © The Royal Society of Chemistry 2012.